Prenatal diagnosis of congenital harlequin ichthyosis with fetal MRI - Kiran A Kale; Nitin P Ghonge; Anita Kaul (Indian Journal of Radiology and Imaging, 2019)
Most of the fetal deformities are caused due to genetic abnormalities. Although magnetic resonance imaging (MRI) may be used to accurately diagnose these deformities, it has been reported that gene analysis is a more accurate diagnostic method. Harlequin ichthyosis (HI) or Ichthyosis fetalis (IF) is a rare and extremely severe hereditary skin disorder with autosomal recessive inheritance. The ultrasound features have been described well and the diagnosis can be made with a fair degree of confidence. However, the final diagnosis needs to be established by prenatal invasive tests. In the present study, we describe the diagnosis of HI in the third trimester on fetal MRI referred to our department with suspicion of anterior encephalocele which was later confirmed through postnatal genetic evaluation.